Differentiating Structurally Similar Fentanyl Analogs by Comparing Density Functional Theory (DFT) Calculations and Surface-Enhanced Raman Spectroscopy (SERS) Results - Dogruer Erkok, Sevde; Hernandez, Emily; Cruz, Jordi; Mebel, Alexander M; McCord, Bruce (Applied spectroscopy, 2024)
Fentanyl and fentanyl analogs are the main cause of recent overdose deaths in the United States. The presence of fentanyl analogs in illicit drugs makes it difficult to estimate their potencies. This makes the detection and differentiation of fentanyl analogs critically significant. Surface-enhanced Raman spectroscopy (SERS) can differentiate structurally similar fentanyl analogs by yielding spectroscopic fingerprints for the detected molecules. In previous years, five fentanyl analogs, carfentanil, furanyl fentanyl, acetyl fentanyl, 4-fluoroisobutyryl fentanyl (4-FIBF), and cyclopropyl fentanyl (CPrF), gained popularity and were found in 76.4% of the fentanyl analogs trafficked. In this study, we focused on 4-FIBF, CPrF, and structurally similar fentanyl analogs. We developed methods to differentiate these fentanyl analogs using theoretical and experimental methods. To do this, a set of fentanyl analogs were examined using density functional theory (DFT) calculations. The DFT results obtained in this project permitted the assignment of spectral bands. These results were then compared with normal Raman and SERS techniques. Structurally similar fentanyl analogs show important differences in their spectra, and they have been visually differentiated from each other both theoretically and experimentally. Additional results using principal component analysis and soft independent modeling of class analogy show they can be distinguished using this technique. The limit of detection values for FIBF and CPrF were determined to be 0.35 ng/mL and 4.4 ng/mL, respectively, using SERS. Experimental results obtained in this project can be readily implemented in field applications and smaller laboratories, where inexpensive portable Raman spectrometers are often present and used in drug analysis.